Developing student teachers’ approaches to group teaching in placement learning - Pham , Duc Hiep (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
The purpose of this research aims to develop teaching methodology of pedagogical studentsthrough small-group teaching practice in group of 4-5 students. All activities that have been conductedby researching the lesson to advance the teaching method of students are: (1) setting goals: identifyspecific student needs and formulate curricular goals, (2) plans: develop lesson plans; devise data -collection strategies; rationalize the approach; anticipate students’ responses, (3) implementation: one or two members of the team teach the public lessons in high schools where students from University of Education have placement learning, while other members observe and collect data, such as video documentation and working samples, (4) debrief: analyze collected data; discuss about students’learning, teachers’ teaching, relative pedagogical content learning. We used Kobo software and Maastricht-Peer Activity Rating Scale in order to observe and evaluate the teaching – learning activities in small group of students. The results show that using reflection thinking while teaching bysmall group would help students to improve their teaching methods more efficiently.